ELECTRICAL STIMULATION USING THE BLINKING REFLEX SYSTEM IN THE COMPLEX TREATMENT OF PATIENTS WITH TRAUMATIC NEUROPATHY OF THE MANDIBULAR NERVE AFTER DENTAL IMPLANTATION - Zarnigor Jabborova Bozorboy's daughter; Aziz Kubayev Saidolimovich (Scholar Express Journals, 2023)
In this article, electrical stimulation using the blink reflex system in the complex treatment of patients with traumatic neuropathy of the mandibular nerve after dental implantation, electrical stimulation according to the blink reflex system, the peripheral connection of the trigeminal nerve, the reticular formation of the brain stem are described in detail.
Keywords: dental implant; mandibular nerve,; traumatic neuropathy; reticular formation